The Covernotes Notary or Settlement of Liability Rights in Banking Credits - Harviyana, Marisa; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
Covernotes are usually issued by a Notary because the Notary has not completed his work relating to the requirements that have not been met by the parties to issue a deed. The problems in this study are: The legal basis and authority of a notary in issuing a covernote, Liability of a notary's covernote in completing the making of the Mortgage, The legal consequences that arise if the Notary fails to provide a covernote for the completion of the making of the Mortgage if the loan is bad. The purpose of this study is to know and analyze the regulation or legal basis and authority of a Notary in issuing Covernotes, to know and to analyze the responsibilities of a Notary to Covernotes in completing the making of Mortgage Rights. The research method used is normative juridical, research specifications are analytical descriptive. Data sources consist of primary, secondary, tertiary legal materials. Data collection was carried out by means of a literature study. Presentation of data presented in a narrative. Juridical-qualitative data analysis. Based on the results of the conclusion that Covernote is not regulated in legislation or positive law in Indonesia. Publishing and drawing up covernotes by a notary has no legal basis. The notary's responsibility for the covernote made in granting credit by the bank is limited only to the covernote made by the notary which has expired. Legal consequences for the Notary if he fails to carry out the covernote, the Notary can be held accountable for completing it immediately. Suggestions from the conclusion that it is necessary to have arrangements in making covernotes, such as regulating the formation procedures, conditions that must be met until publication into the Notary Office Act. Notaries are more careful in carrying out their duties, especially in issuing covernotes.Keywords: Banking; Covernote; Mortgage; Notary.